Logistics Of Pedagogical Innovation In The Environment Of The Educational Cluster - Allayorova S. B. (Euro Asian Journal Publishing, 2024)
In the article discuses about the logistics of pedagogical innovations in the environment of the educational cluster
Keywords: Educational cluster; practice-oriented direction; intelligence